2013
DOI: 10.1155/2013/820468
|View full text |Cite
|
Sign up to set email alerts
|

Profile, Bacteriology, and Risk Factors for Foot Ulcers among Diabetics in a Tertiary Hospital in Calabar, Nigeria

Abstract: Diabetic foot disease is a major medical, social, and economic problem. This retrospective study assessed the profile of diabetes mellitus patients with foot ulcers in the University of Calabar Teaching Hospital (UCTH), Nigeria. Admission records of all patients admitted unto the medical wards of UCTH over a 5 year period were analysed. The records of diabetic patients were retrieved. Data on patient characteristics and possible risk factors for diabetes mellitus foot ulcers was extracted. Of the 3,882 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Long duration of hospital stay was observed among the patients similar to observations reported by other workers [16,19,34]. Ajayi et al [34] reported a mean duration of hospital stay of about 25 days, whereas in Calabar, a mean duration of 38.5 days was reported [16].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Long duration of hospital stay was observed among the patients similar to observations reported by other workers [16,19,34]. Ajayi et al [34] reported a mean duration of hospital stay of about 25 days, whereas in Calabar, a mean duration of 38.5 days was reported [16].…”
Section: Discussionsupporting
confidence: 86%
“…Ajayi et al [34] reported a mean duration of hospital stay of about 25 days, whereas in Calabar, a mean duration of 38.5 days was reported [16]. Long duration of hospital stay may be due to slow healing rate of the ulcers.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The single strain of Candida tropicalis isolated was sensitive to nyststin, amphotericin B, itraconazole, ketoconazole, fluconazole and voriconazole. Diabetic foot disease is a major medical, social and economic problem that is seen in every continent and constitutes a major burden to the patient and the health care system (Otu et al, 2013). People with diabetes have about a 25% chance of developing a foot ulcer in their lifetime (Spichler et al, 2015).…”
Section: Resultsmentioning
confidence: 99%